MODELING OF EQUIVALENT STIFFNESS OF A MAGNETIC SPRING OF VIBRATION EXCITER BASED ON COAXIAL-LINEAR MOTOR - G.M. Golenkov (National Technical University "Kharkiv Polytechnic Institute", 2015)
Purpose. The research of the influence of value and direction of current on the equivalent spring magnetic force based on coaxial-linear motor (CLM – MS). Methodology. We carried out investigation of the equivalent harshness of magnetic spring with determination of electromechanical propulsion performance characteristics by the methods of computer modeling and experimental research of physical model of CLM – MS. The modeling of magnetic spring of CLM – MS is carried out by the finite-element method. The challenge is met as an axisymmetric challenge in cylindrical co-ordinates in magnetostatic approach. The experimental investigattion of the propulsion performance characteristics of magnetic spring is carried out on the test bench. Results. After the computer modeling and the experimental investigation of the electromechanical propulsion performance characteristics of magnetic spring the expressions of equivalent stiffness coefficient depending on the current in winding are obtained. The results of computer modeling are confirmed experimentally. Originality. The determination of equivalent stiffness coefficient of magnetic spring of vibration exciter based on coaxial-linear motor. Practical value. The obtained determination of equivalent stiffness coefficient of magnetic spring may be used in process of designing of vibration machines with devices for change of natural oscillation frequency.